2020
DOI: 10.1038/s41598-020-70652-4
|View full text |Cite
|
Sign up to set email alerts
|

The Oligo–Miocene closure of the Tethys Ocean and evolution of the proto-Mediterranean Sea

Abstract: The tectonically driven Cenozoic closure of the Tethys Ocean invoked a significant reorganization of oceanic circulation and climate patterns on a global scale. this process culminated between the Mid Oligocene and Late Miocene, although its exact timing has remained so far elusive, as does the subsequent evolution of the proto-Mediterranean, primarily due to a lack of reliable, continuous deep-sea records. Here, we present for the first time the framework of the Oligo-Miocene evolution of the deep Levant Basi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(60 citation statements)
references
References 47 publications
1
59
0
Order By: Relevance
“…The otoliths of Gnathophis elongatus are elongated and more similar to Conger, unlike Pliocene-Holocene specimens of Gnathophis mystax that are more quadrate (Tuset et al, 2008;Agiadi et al, 2020Agiadi et al, , 2019Agiadi et al, , 2018. However, the orientation of the sulcus forms an angle with the otolith length direction, as in Gnathophis species.…”
Section: Remarksmentioning
confidence: 88%
See 3 more Smart Citations
“…The otoliths of Gnathophis elongatus are elongated and more similar to Conger, unlike Pliocene-Holocene specimens of Gnathophis mystax that are more quadrate (Tuset et al, 2008;Agiadi et al, 2020Agiadi et al, , 2019Agiadi et al, , 2018. However, the orientation of the sulcus forms an angle with the otolith length direction, as in Gnathophis species.…”
Section: Remarksmentioning
confidence: 88%
“…The dorsal rim is straight. Compared to the modern species Mullus surmuletus Linnaeus and Mullus barbatus Linnaeus (Hoedemakers and Batllori, 2005;Tuset et al, 2008;Agiadi et al, 2019), the otoliths of M. elognatus are not as high, but more elongated (OL : OH = 1.76-1.82 in M. elongatus but 1.23 in M. barbatus and 1.52 in M. surmulatus, both values from the Pleistocene of the eastern Mediterranean; Agiadi et al, 2019), more so than Mullus bifurcatus Strashimirov reported from the lower-middle Miocene of the Paratethys (Bratishko et al, 2015).…”
Section: Remarksmentioning
confidence: 99%
See 2 more Smart Citations
“…DEC and DIVALIKE appear to favor a largely distributed MRCA which is compatible with paleogeographical and paleoclimatic events. During the Early and Middle Miocene, closure of the gateway of Proto-Mediterranean Sea [66] followed by the Messinian Salinity Crisis [67] and coupled with the uplift of the Atlas and Zagros Mountains [68], have strongly affected climatic conditions in the area under consideration. These mountain ranges, as well as the uplift of the Qinghai-Tibetan Plateau on the East, have acted as topographic barriers to moisture and have largely contributed to the aridification of the area.…”
Section: Evolutionary History and Biogeography Of Paraphlebotomus Sensu Novmentioning
confidence: 99%